The Role of Tests and Tools in Accurate Diagnosis and Severity in Children with Autism Spectrum Disorders - Mohammadi Ghanatghestani, Leili; Shahriari Ahmadi, Mansure; Tajali, Parisa (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The current research was conducted with the aim of studying and investigating the role of tests and tools in the accurate diagnosis of autism spectrum disorders.Methods: A total of 83 children (56 boys and 27 girls) diagnosed with autism or one of the comorbid diagnoses were selected and underwent the GARS-3 scale and the Psycho-Educational Profile Revised (PEP-3) diagnostic test. Additionally, parents were asked to complete a checklist provided by the researcher. The age range of the individuals with autism was between 2 and 7 years, with an average age of 6.5 years.Findings: The results of the statistical analyses of the data from this study indicated a significant role of diagnosis tools.Conclusion: So, the proper and timely use of diagnostic tests plays a significant role in the accurate diagnosis of autism spectrum disorders and also in determining the severity of these disorders.